2015
DOI: 10.1002/aur.1440
|View full text |Cite
|
Sign up to set email alerts
|

Learning Language in Autism: Maternal Linguistic Input Contributes to Later Vocabulary

Abstract: It is well established that children with typical development (TYP) exposed to more maternal linguistic input develop larger vocabularies. We know relatively little about the linguistic environment available to children with autism spectrum disorders (ASD), and whether input contributes to their later vocabulary. Children with ASD or TYP and their mothers from English and French-speaking families engaged in a 10 min free-play interaction. To compare input, children were matched on language ability, sex, and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
80
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(93 citation statements)
references
References 33 publications
11
80
2
Order By: Relevance
“…Importantly, despite the social impairments associated with ASD, children are sensitive to many of the same reciprocal aspects of parental language as TD children. In general, parents of children with ASD provide a similar quantity and quality of language input as parents of TD children in naturalistic play interactions [Bang & Nadig, ] and when presenting new words [Adamson, Bakeman, Deckner, & Nelson, ; Hani et al, ], and just as with TD children, quantity and quality of input predict language skill [Bang & Nadig, ]. In fact, as Naigles [] points out, “What is most remarkable about the extant research … is how similar the role of input seems to be for children with ASD, demonstrating effects of maternal responsiveness, effects of the child's role in establishing and maintaining joint attention, and effects of specific components of maternal speech on subsequent language development” (p. 245).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, despite the social impairments associated with ASD, children are sensitive to many of the same reciprocal aspects of parental language as TD children. In general, parents of children with ASD provide a similar quantity and quality of language input as parents of TD children in naturalistic play interactions [Bang & Nadig, ] and when presenting new words [Adamson, Bakeman, Deckner, & Nelson, ; Hani et al, ], and just as with TD children, quantity and quality of input predict language skill [Bang & Nadig, ]. In fact, as Naigles [] points out, “What is most remarkable about the extant research … is how similar the role of input seems to be for children with ASD, demonstrating effects of maternal responsiveness, effects of the child's role in establishing and maintaining joint attention, and effects of specific components of maternal speech on subsequent language development” (p. 245).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, despite the social impairments associated with ASD, children are sensitive to many of the same reciprocal aspects of parental language as TD children. In general, parents of children with ASD provide a similar quantity and quality of language input as parents of TD children in naturalistic play interactions [Bang & Nadig, 2015] and when presenting new words [Adamson, Bakeman, Deckner, & Nelson, 2014;Hani et al, 2013], and just as with TD children, quantity and quality of input predict language skill [Bang & Nadig, 2015]. In fact, as Naigles [2013] points out, "What is most remarkable about the extant research .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, no study has examined the role of linguistic input in the acquisition of person-reference in ASD. This is an inviting avenue for research considering past work has shown that parental input influences language ability more broadly for all children, including those with ASD [e.g., Bang & Nadig, 2015;Fusaroli, Weed, Fein, & Naigles, 2019;Hoff & Naigles, 2002;Rowe, 2012;Venker et al, 2015;Warren et al, 2010;Wolchik, 1983]. Although no study has looked at the role of input in person-reference directly, He, Luyster, Hong, and Arunachalam [2018] compared maternal input to infants between 3 and 19 months at high and low risk for ASD by virtue of having an older sibling with ASD.…”
Section: Limitations Of Past Researchmentioning
confidence: 99%
“…Consequently, communicating in a less proficient language may impact the quantity and complexity of language input and the quality of interactions [e.g., parent–child synchrony and verbal expansions on child utterances; Hudry et al, ]. This could be detrimental, as both the quantity and complexity of language input [e.g., Bang & Nadig, ] and the quality of parent–child interactions [Siller & Sigman, ] are important facilitators of language development. The current study examines the impact of amount of language exposure on the vocabulary and morphological skills of children with ASD growing up in a bilingual context, enabling evidence‐informed decisions to be made by families and professionals.…”
Section: Introductionmentioning
confidence: 99%